Cardiac manifestations in HIV-infected Thai children - Pongprot Y. (2014)
Cardiac complications contribute significantly to morbidity and mortality in HIV-infected children. There have been few reports of cardiac manifestations in HIV-infected children in developing countries. The aims of this study were to evaluate the clinical manifestations and echocardiographic findings in Thai children with HIV infection and determine the clinical predictors of left ventricular dysfunction and pulmonary hypertension. We retrospectively reviewed the medical records of 27 infants infected with HIV perinatally who presented with cardiovascular problems at a tertiary care hospital between 1995 and 2000. The mean age at initial cardiac evaluation was 36 months (range 8-65). Signs and symptoms included dyspnoea in all cases, oedema in 12 (44%), finger clubbing in 11 (41 %), cyanosis in 6 (22%) and S3 gallop in 8 (30%). Echocardiographic abnormalities included pericardial effusion in 12 (44 %), right ventricular dilatation in 12 (44%), pulmonary hypertension in 11 (41 %), diminished left ventricular fractional shortening in 10 (37%), left ventricular dilatation in 9 (33%) and combined ventricular dilatation in 2 (7%). Left ventricular dysfunction did not correlate with HIV CDC classification, age, nutritional status or clinical signs and symptoms. © 2004 The Liverpool School of Tropical Medicine.